Effect of Motor-Cognitive Dual Task Training on Cognitive Function in patients with Dementia - Sari Triyulianti; Siti Muawanah; Nova Relida Samosir; Adinda Soleha (POLTEKKES KEMENKES PONTIANAK, 2025)
Dementia is a progressive neurological condition characterised by a decline in cognitive function, memory and behaviour, which significantly affects an individual's activities of daily living. As the number of elderly increases, the prevalence of dementia also shows an increasing trend and is a major challenge in geriatric health services. This study aims to evaluate the effectiveness of motor-cognitive dual-task training in improving cognitive function in the elderly with dementia. This research uses a case study method on one subject who meets the inclusion and exclusion criteria. The intervention was conducted for four weeks, totaling 12 sessions with a frequency of three times per week. Each session lasted 30-45 minutes and consisted of a combination of physical activities performed in conjunction with cognitive tasks. The exercises were designed to stimulate various domains of cognitive function as measured by the Mini-Mental State Examination (MMSE), including orientation, attention and calculation, short-term memory, language, and visuospatial abilities. Evaluation of cognitive function was conducted using the MMSE before and after the intervention. The results showed an increase in MMSE score from 21 to 24, indicating an improvement in cognitive function by 14.3%, although still in the mild dementia category. These findings support that motor-cognitive dual-task training can be an effective physiotherapy approach to improve cognitive function in patients with dementia.